# Solve for z y=(9/5*(dz))+32

y=(95⋅(dz))+32
Rewrite the equation as (95⋅(dz))+32=y.
(95⋅(dz))+32=y
Simplify each term.
Multiply 95(dz).
Combine d and 95.
d⋅95z+32=y
Combine d⋅95 and z.
d⋅9z5+32=y
d⋅9z5+32=y
Move 9 to the left of d.
9dz5+32=y
9dz5+32=y
Subtract 32 from both sides of the equation.
9dz5=y-32
Multiply both sides of the equation by 59.
59⋅9dz5=59⋅(y-32)
Simplify both sides of the equation.
Simplify 59⋅9dz5.
Cancel the common factor of 5.
Cancel the common factor.
59⋅9dz5=59⋅(y-32)
Rewrite the expression.
19⋅(9dz)=59⋅(y-32)
19⋅(9dz)=59⋅(y-32)
Cancel the common factor of 9.
Factor 9 out of 9dz.
19⋅(9(dz))=59⋅(y-32)
Cancel the common factor.
19⋅(9(dz))=59⋅(y-32)
Rewrite the expression.
dz=59⋅(y-32)
dz=59⋅(y-32)
dz=59⋅(y-32)
Simplify 59⋅(y-32).
Apply the distributive property.
dz=59y+59⋅-32
Combine 59 and y.
dz=5y9+59⋅-32
Multiply 59⋅-32.
Combine 59 and -32.
dz=5y9+5⋅-329
Multiply 5 by -32.
dz=5y9+-1609
dz=5y9+-1609
Move the negative in front of the fraction.
dz=5y9-1609
dz=5y9-1609
dz=5y9-1609
Divide each term by d and simplify.
Divide each term in dz=5y9-1609 by d.
dzd=5y9⋅1d-1609⋅1d
Cancel the common factor of d.
Cancel the common factor.
dzd=5y9⋅1d-1609⋅1d
Divide z by 1.
z=5y9⋅1d-1609⋅1d
z=5y9⋅1d-1609⋅1d
Simplify each term.
Multiply 5y9 and 1d.
z=5y9d-1609⋅1d
Multiply 1d and 1609.
z=5y9d-160d⋅9
Move 9 to the left of d.
z=5y9d-1609d
z=5y9d-1609d
z=5y9d-1609d
Solve for z y=(9/5*(dz))+32

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top